Congenital Amegakaryocytic Thrombocytopenia: A Brief Review of the Literature - Fatma S. Al-Qahtani (SAGE Publishing, 2010)
Congenital amegakaryocytic thrombocytopenia (CAMT) is a rare inherited autosomal recessive disorder that presents with thrombocytopenia and absence of megakaryocytes. It presents with bleeding recognized on day 1 of life or at least within the first month. The cause for this disorder appears to be a mutation in the gene for the thrombopoeitin (TPO) receptor, c-Mpl, despite high levels of serum TPO. Patients with severe Type I-CAMT carry nonsense Mpl mutations which causes a complete loss of the TPO receptor whereas those with Type II CAMT carry missense mutations in the Mpl gene affecting the extracellular domain of the TPO receptor. Differential diagnosis for severe CAMT includes thrombocytopenia with absent radii (TAR) and Wiskott-Aldrich syndrome (WAS). The primary treatment for CAMT is bone marrow transplantation. Bone Marrow/Stem Cell Transplant (HSCT) is the only thing that ultimately cures this genetic disease. Newer modalities are on the way, such as TPO-mimetics for binding towards partially functioning c-Mpl receptors and gene therapy. Prognosis of CAMT patients is poor, because all develop in childhood a tri-linear marrow aplasia that is always fatal when untreated. Thirty percent of patients with CAMT die due to bleeding complications and 20% -due to HSCT if it has been done.